Constructivist Learning Environment: A Perfect Mediator for The Relationship of Students' Multiple Intelligences with Attitudes Towards and Achievement in STEM - Peşman, Haki; Güler, Tuba; Arı, Üzeyir; Erdogan, Fatma (My University, 2024)
In STEM disciplines, it is crucial to design research studies clarifying the relationships between academic performance-related constructs and academic performance. This study aims at exploring whether middle school students’ perceptions of constructivist learning environment (P-CLE) mediate the relationship between their perceptions of multiple intelligences (P-MI) and their attitude towards and achievement in STEM disciplines (AA-STEM). Because the relationships among middle school students’ P-CLE, P-MI, and AA-STEM are under investigation, this study is a correlational study. The sample consisted of 579 students from randomly selected 10 middle schools in Kayapınar, a district of Diyarbakır, Turkiye. The students’ GPA scores in STEM-related courses were used to represent their achievement in STEM disciplines. In addition, the Attitude towards STEM Survey (AtSTEM), Multiple Intelligences Inventory (MII), and Constructivist Learning Environment Survey (CLES) were used for the data collection. Lavaan, an R package, was used to conduct structural equation modeling for mediation analysis. The mediation analysis yielded that the P-CLE was a perfect mediator for the relationship between the P-MI and AA-STEM. In consequence, this study emphasizes the importance of providing constructivist learning environments in STEM classes and encouraging students to think of intelligence as something malleable.
Keywords: STEM; constructivist learning environment; achievement; multiple intelligences